Characteristics, clinical outcomes and patient-reported outcomes of patients with ulcerative colitis receiving tofacitinib: a real-world survey in the United States and five European countries - Alessandro Armuzzi; Ailsa Hart; Joseph C. Cappelleri; Nadir Mammar; Peter Hur; Benjamin Hoskin; Fritha Hennessy; Gary Milligan; Axel Dignass (BMC Gastroenterology, 2023)
Abstract Background To describe variations in treatment patterns, clinical outcomes, patient-reported outcomes (PRO), and physician and patient satisfaction in patients with moderate-to-severe ulcerative colitis (UC) treated with tofacitinib in a real-world setting. Methods Data were drawn from the Adelphi UC Disease Specific Programme™, a point-in-time survey of physicians and their consulting patients in the US and Europe. For inclusion in this analysis, gastroenterologists completed medical record forms for the next seven consecutive consulting patients with confirmed UC, plus a further two patient record forms for patients treated with tofacitinib. Those same patients then completed a patient-reported questionnaire. Results Gastroenterologists (n = 340) provided data for 2049 patients with UC, including 642 patients receiving tofacitinib. Physicians’ most frequent reason for choosing tofacitinib was overall efficacy (71.3% of patients). The proportion of patients in remission increased with length of treatment, from 13.7% at [0, 4) weeks to 68.3% at [52+] weeks. Both physicians and patients reported that the Mayo components of stool frequency and blood in stool were reduced with time on treatment. Improvement in symptoms (bloody diarrhea, abdominal pain/cramps, urgency, rectal bleeding, fatigue/tiredness) was reported in the first weeks of treatment, and increased with time. At week [52+], mean score reductions from treatment initiation to current in overall symptom severity, pain, and fatigue were 2.2 (to a current mean score of 1.1), 2.2 (to 0.9), and 2.1 (to 1.0), respectively. Comparing patients at weeks [0, 4) and [52+] (all PROs, p < 0.0001), the increase in EQ-5D-5L index total score was 0.29 points and in SIBDQ total score was 20.5 points; percent reductions in WPAI absenteeism was 34.4%, presenteeism 26.8%, overall work impairment 40.9% and activity impairment was 28.3%. These changes reached the thresholds for minimally clinically important differences. The majority of physicians (91.9%) and patients (93.5%) were satisfied with tofacitinib at week [52+]. Conclusion Patients with moderate-to-severe UC treated with tofacitinib show considerable improvement in symptoms and quality of life from tofacitinib initiation to one year and beyond, with high rates of remission. Physicians and patients report satisfaction with UC control at recommended doses in a mostly biologic experienced population.